"Let's Talk About Justice": English, Social Studies, and Judaic Studies Teachers Deliberate About Justice Across the Middle School Curriculum. Issue 2 (3rd April 2022) - Shargel, Rebecca
ABSTRACT: Although several prior studies portray integration in Jewish high schools, this study presents a unique example from a Jewish middle school, where a team of 7th-grade teachers met over two years to integrate their disciplines. Investigating factors that facilitated and hindered integration, I found that the following factors helped drive integration forward: administrative support, teachers' interest, and creating new frameworks. Conversely, factors hindering integration included teachers' struggles to find connections among subjects and the lack of "follow through" by the administration. The study concludes with implications for professional development.